2022
DOI: 10.48550/arxiv.2201.02357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ghost instability in the teleparallel gravity model with parity violations

Mingzhe Li,
Zhihao Li,
Haomin Rao

Abstract: In this paper we consider the parity violating gravity model within the framework of teleparallel gravity. The parity violations are caused by the couplings of a scalar field to the scalar invariants which are parity-odd and quadratic in the torsion tensor. Totally there are two such type independent invariants, and one of them is the Nieh-Yan density. Through investigations on the cosmological perturbations of this model, we find that in general it suffers from the difficulties of ghost instability in the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Finally, a local Lorentz covariant version of [349] was considered in [351] and non-flat universes were also taken into account. It was recently reported that some TG parity-violating models suffer from ghost instabilities but the so-called modified TG Nieh-Yan is free of them [352].…”
Section: Other Approachesmentioning
confidence: 99%
“…Finally, a local Lorentz covariant version of [349] was considered in [351] and non-flat universes were also taken into account. It was recently reported that some TG parity-violating models suffer from ghost instabilities but the so-called modified TG Nieh-Yan is free of them [352].…”
Section: Other Approachesmentioning
confidence: 99%
“…Alternatively, if we start from Teleparallel Equivalent of General Relativity (TEGR) [33][34][35][36], we will obtain a family of torsion-based modified gravity [37,38]. These torsional gravities provide new possible mechanisms for cosmological observations, such as inflation and accelerated expansion, and are highly considered and widely studied [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. It is worth noting that these modifications are efficient under confrontation with galaxy-scale observations too [56,57].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was found in Ref. [21] that generalizations of NYTG by considering the couplings of φ to other parity-odd terms quadratic in the torsion tensor [22] are perplexed by the ghost problem again. It means in this scenario the NYTG model is the unique one that can avoid the ghost problem.…”
Section: Introductionmentioning
confidence: 99%